Musicality as a trace of historical events in contemporary Polish drama - Vasylieva, Oleksandra (To Tell the History: Polish Contemporary Dramaturgy after 2006, 2023)
The article analyzes the role of musicality in presenting historical events in contemporary Polish drama. Music is not only an ideological vehicle but above all one of the medias for transmitting memory, a trace of past events that are reflected in the present. It is this category of reflection, or resonance, that makes the appearance of music in dramatic texts similar to an echo. Its essence is the ability to convey emotions that cannot always be explained with words and often remain at the level of experience. That is why musicality serves as a filter through which the texts of contemporary Polish playwrights are being critically analyzed. In this case, we use the term musicality in its broad sense. Musicality in dramatic texts covers not only the musical pieces themselves but also the entire sonosphere. Musicality is a powerful way of presenting Polish history in contemporary drama on various levels.